METODOLOGI PERBANDINGAN MADZHAB DALAM AL-MUGHNI KARYA IBNU QUDAMAH: PENDEKATAN DAN IMPLIKASINYA DALAM STUDI HUKUM ISLAM - Khairatun Hisan; Dzulkifli Hadi Imawan; Haqqiya, Hannafa (Mazahibuna: Jurnal Perbandingan Mazhab, 2025)
This study investigates the methodology of muqāranah al-mażāhib (comparative of madhhabs) as applied by Ibn Qudāmah in his seminal work, Kitāb al-Mugnī, a key reference in the landscape of Islamic jurisprudence in Indonesia. The primary purpose is to critically analyze Ibn Qudāmah’s comparative legal approach and assess its relevance for contemporary ijtihad. Employing a qualitative method, the research utilizes content analysis and textual hermeneutics to examine selected chapters of al-Mugnī—specifically those related to acts of worship and mu‘āmalah (social transactions). The findings reveal that Ibn Qudāmah's method systematically compares the legal views of the four major Sunni madhhabs and includes perspectives from other jurists, presenting them with detailed argumentation and rational justification. His use of tarjīḥ (preference) reflects a critical evaluative process that selects the most compelling legal opinion based on textual evidence and reasoning. The originality of this study lies in its focused analysis of Ibn Qudāmah's structured comparative technique, which balances scholarly objectivity with methodological rigor. The implications of this research are significant for contemporary Islamic legal scholarship, particularly in advancing the practice of collective ijtihad, refining fatwa formulation processes, and fostering a tolerant yet disciplined engagement with legal diversity. Furthermore, the integration of maqāṣid al-sharī‘ah into this comparative framework enriches its applicability in addressing modern socio-legal issues.